Rhodium-iron bimetallic catalyst as well as preparation method and application thereof
By preparing rhodium iron bimetallic catalyst in the presence of a dispersant, the problem of insufficient catalyst activity and selectivity in the carbon dioxide methanation reaction under low temperature conditions was solved, and efficient carbon dioxide conversion and high methane selectivity were achieved.
Patent Information
- Application Number
- CN202411772290.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-04
AI Technical Summary
In the existing carbon dioxide methanation reaction, the carbon dioxide conversion rate and methane selectivity of the catalyst under low temperature conditions are relatively low.
The rhodium iron bimetallic catalyst was prepared by sequential reduction method in the presence of a dispersant to form highly dispersed rhodium iron bimetallic nanoparticles supported on a nanoTiO2 support.
Under 270°C, the catalyst exhibits high carbon dioxide conversion and high methane selectivity, significantly improving catalytic activity and reducing the generation of by-products.
Smart Images

Figure CN119588376A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon dioxide hydrogenation catalyst preparation, and in particular to a rhodium-iron bimetallic catalyst and a preparation method and application thereof. Background Art
[0002] With the massive burning of fossil fuels around the world, the amount of carbon dioxide emitted into the atmosphere has increased dramatically, accounting for more than 80% of the total greenhouse gas emissions, exacerbating the impact of the greenhouse effect on the global ecosystem. By coupling carbon dioxide with "green hydrogen" to convert it into commercially valuable products, such as carbon monoxide, methane, methanol and hydrocarbons and other value-added industrial products, achieving economic and environmental benefits is an important means of carbon dioxide resource utilization. Among them, the carbon dioxide methanation reaction is considered to be an effective way to utilize carbon dioxide by converting carbon dioxide into methane, an important fuel with high calorific value and clean products.
[0003] The carbon dioxide methanation reaction is an exothermic reaction. According to thermodynamic studies, the reaction is favorable in the low temperature range of 25 to 400 ° C, but it is difficult to activate carbon dioxide at low temperatures, and the kinetics limit the industrial application of the reaction. Therefore, the development of efficient carbon dioxide methanation catalysts under low temperature conditions is the main research direction at present. Compared with non-precious metal-based catalysts, precious metal-based catalysts (Ru, Rh, etc.) have good low-temperature activity and anti-carbon deposition performance, among which precious metals Ru and Rh both show good activity and selectivity in the carbon dioxide methanation reaction. Chinese patent CN 111036199 A prepared a highly dispersed catalyst supported by rutile titanium dioxide by a simple impregnation method, and showed high methane selectivity, but the carbon dioxide conversion rate of the catalyst was low, and the catalytic activity needed to be further optimized. Chinese patent CN104148065A uses precious metal Ru or Rh as the main active component, and prepares catalysts with different carriers and additives by coating. It shows good activity and selectivity in the carbon dioxide methanation reaction, but the reaction conditions are harsh and the preparation process is complicated.
[0004] In summary, in the current carbon dioxide methanation reaction, low-temperature carbon dioxide methanation catalysts still face problems such as low carbon dioxide conversion rate and low methane selectivity. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a catalyst for preparing methane by hydrogenating carbon dioxide and a preparation method thereof. The highly dispersed rhodium-iron bimetallic catalyst prepared by the method of the present invention has the characteristics of high carbon dioxide conversion rate and high methane selectivity in the carbon dioxide methanation reaction.
[0006] One of the purposes of the present invention is to provide a method for preparing a rhodium-iron bimetallic catalyst.
[0007] The second purpose of the present invention is to provide a rhodium-iron bimetallic catalyst prepared by the preparation method.
[0008] The third object of the present invention is to provide an application of the rhodium-iron bimetallic catalyst.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] In a first aspect, the present invention provides a method for preparing a rhodium-iron bimetallic catalyst, comprising the following steps:
[0011] S1, dissolving nano-TiO2, rhodium salt and dispersant in water and stirring evenly to obtain solution A, wherein the content of rhodium ions is 1wt%-10wt% based on the mass of nano-TiO2; dissolving the reducing agent in water and obtaining a uniformly dispersed solution B after ultrasonic treatment; adding solution B dropwise to solution A and stirring to obtain solution C;
[0012] S2, adding iron salt to solution C and continuing to stir evenly to obtain a mixed solution, wherein the molar ratio of rhodium to iron is 1:0.2-5;
[0013] S3. Wash and dry the obtained mixed solution to obtain a rhodium-iron bimetallic catalyst.
[0014] The highly dispersed rhodium and iron dual active center catalyst is prepared by reducing rhodium first and then reducing iron by a sequential reduction method in the presence of a dispersant, and no further calcination treatment is required after reduction. In the presence of a dispersant, a highly dispersed rhodium catalyst is first obtained, and after further reducing iron, due to the electronic interaction between the two, a rhodium-iron bimetal is formed, which not only changes the electronic structure of rhodium and weakens its over-hydrogenation ability, but also promotes the non-dissociative activation of carbon monoxide intermediates, thereby achieving excellent catalytic performance.
[0015] Step S1:
[0016] In step S1, the nano titanium dioxide is commercial nano titanium dioxide, preferably with an average particle size of 20 nm to 30 nm, and a rutile phase structure.
[0017] In some embodiments, in step S1, the rhodium salt is one or more of rhodium chloride, rhodium nitrate, rhodium phosphate, and rhodium acetylacetonate;
[0018] In some embodiments, in step S1, the dispersant is polyvinyl pyrrolidone (PVP), and the model K value of PVP is 16 to 32;
[0019] In some embodiments, in step S1, the ratio of the molar amount of PVP to the total molar amount of rhodium and iron is 2 to 10:1;
[0020] In some embodiments, in step S1, the concentration of rhodium salt in solution A is 0.0006-0.05 g / mL;
[0021] In some embodiments, in step S1, the stirring speed is 200 rpm to 1000 rpm, and the stirring time is 0.5 h to 5 h.
[0022] In some embodiments, in step S1, the reducing agent is one or more of sodium borohydride, sodium borohydride, ammonia borane, and hydrazine hydrate;
[0023] The concentration of the reducing agent in solution B is 10-100 g / mL.
[0024] In some embodiments, in step S1, the ratio of the molar amount of the reducing agent to the total molar amount of rhodium and iron ions is 5 to 20:1.
[0025] In some embodiments, in step S1, the ultrasonic time is 0.5h to 1h.
[0026] In some embodiments, in step S1, the dropping speed is 0.1 to 0.5 mL / min, the stirring speed is 200 to 1000 r / min, and the stirring time is 0.5 to 2 h.
[0027] Step S2:
[0028] In some embodiments, in step S2, the iron salt is one or more of ferric nitrate, ferric sulfate, ferric chloride, and ferric tribromide;
[0029] In some embodiments, in step S2, the stirring speed is 200 rpm to 1000 rpm, and the stirring time is 0.5 h to 2 h.
[0030] Step S3:
[0031] In some embodiments, in step S3, centrifugal washing is performed using a mixed solution of acetone and water, wherein the volume ratio of acetone to water is 1 to 5:1;
[0032] In some embodiments, in step S3, the drying operation process is vacuum drying, the drying temperature is 30 to 100° C., and the drying time is 3 to 24 hours.
[0033] In a second aspect, the present invention provides a rhodium-iron bimetallic catalyst prepared by the above-mentioned preparation method, wherein the rhodium-iron bimetallic catalyst comprises a nano-TiO2 carrier, and highly dispersed rhodium-iron bimetallic nanoparticles supported on the nano-TiO2 carrier, wherein the average particle size of the rhodium-iron bimetallic nanoparticles is 5 to 20 nm;
[0034] Based on the mass of the TiO2 carrier, the loading amount of rhodium is 1wt%-10wt%, and the molar ratio of rhodium to iron is 1:1-5.
[0035] In some embodiments, the average particle size of the nano-TiO2 carrier is 20 nm to 30 nm, and the physical phase is a rutile phase structure.
[0036] In a third aspect, the present invention provides an application of the above-mentioned rhodium-iron bimetallic catalyst in the catalytic reaction of carbon dioxide hydrogenation to produce methane.
[0037] Preferably, the catalytic reaction is carried out in a fixed bed reactor;
[0038] The catalyst is tableted, crushed, sieved, and loaded into a fixed bed reactor for carbon dioxide hydrogenation reaction, wherein the sieved particle size is 10 to 80 meshes;
[0039] The reaction conditions are: reaction temperature of 200-400° C., reaction pressure of 2-4 MPa, gas space velocity of 3000-8000 mL / g / h, and the gas used is a mixture of CO2 and H2, wherein the volume ratio of CO2 to H2 is 1:1-5.
[0040] Preferably, the rhodium-iron bimetallic catalyst is subjected to hydrogen pre-reduction treatment before use, and the reduction conditions are: hydrogen space velocity of 3000mL / g / h to 10000mL / g / h, temperature of 200°C to 400°C, and reduction time of 0.5h to 5h.
[0041] Technical effects:
[0042] (1) The preparation method of the present invention is simple, the catalyst does not need to be calcined, and the operation process is convenient;
[0043] (2) The rhodium-iron bimetallic catalyst prepared by the present invention is pre-reduced under the condition of a dispersant to avoid rhodium atoms from agglomerating, so that they are uniformly dispersed on the surface of the titanium dioxide carrier, and the iron is further reduced to form highly dispersed rhodium-iron bimetallic catalytic active sites, thereby improving the atomic utilization efficiency of the active components in the catalyst;
[0044] (3) The rhodium-iron bimetallic can significantly enhance the activation ability of carbon dioxide and the hydrogenation ability of intermediate products, which helps to improve the activity of the catalyst and avoid by-products such as carbon monoxide, improve the selectivity of methane, and further regulate the dispersion of the rhodium-iron bimetallic by changing the molar ratio of rhodium and iron, thereby regulating the catalytic performance;
[0045] (4) The catalyst prepared by the present invention exhibits excellent catalytic performance at a relatively low temperature (270° C.), and has high methane selectivity while having a high carbon dioxide conversion rate.
[0046] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 X-ray diffraction (XRD) spectra of the catalysts prepared in Example 1 and Example 2.
[0048] Figure 2 The following are the test results of the catalysts prepared in Examples and Comparative Examples. DETAILED DESCRIPTION
[0049] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0050] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0051] Example 1
[0052] (1) 25.3 mg of hydrated rhodium chloride (0.01 mmol, 9.9 mg rhodium), 500 mg of nano-titanium dioxide (P25), and 66.6 mg of PVP (0.6 mmol, molecular weight calculated as monomer, PVP monomer molar mass is 111) were dissolved in 30 mL of deionized water, and stirred at 500 rpm for 1 h, which was recorded as solution A. The rhodium loading was 2 wt.%, the K value of PVP was 29-32, and the ratio of the molar amount of PVP to the sum of the molar amounts of rhodium and iron was 2:1;
[0053] (2) 56.7 mg of sodium borohydride was dissolved in 1 mL of deionized water and ultrasonicated for 1 h to obtain a uniformly dispersed solution B, wherein the ratio of the molar amount of sodium borohydride to the sum of the molar amounts of rhodium and iron was 5:1;
[0054] (3) Solution B was slowly added dropwise to solution A over a period of about 5 min, and stirred at 500 rpm for 1 h;
[0055] (4) 80 mg of ferric nitrate nonahydrate (0.2 mmol, 11 mg iron) was added to the above solution and stirred at 500 rpm for 1 h. The molar ratio of rhodium to iron was 1:2 and the iron loading was 2.2 wt.%;
[0056] (5) washing the solution by centrifugation with acetone and water in a volume ratio of 3:1, and repeating the process three times;
[0057] (6) The centrifuged sample was placed in a vacuum drying oven and dried at 80°C for 12 h, and the catalyst was collected for testing;
[0058] The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 8000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation. The reaction temperature was 270℃, the reaction pressure was 3MPa, the space velocity was 6000mL / g / h, and the volume ratio of CO2 / H2 was 1:4. The reaction performance test results are shown in Figure 2 .
[0059] Example 2
[0060] (1) 25.3 mg of hydrated rhodium chloride (0.1 mmol, 9.9 mg of rhodium), 500 mg of nano-titanium dioxide (P25), and 44.4 mg of PVP (0.4 mmol, molecular weight calculated as monomer, PVP monomer molar mass is 111) were dissolved in 30 mL of deionized water, and stirred at 500 rpm for 1 h, which was recorded as solution A. The rhodium loading was 2 wt.%, the K value of PVP was 29-32, and the ratio of the molar amount of PVP to the sum of the molar amounts of rhodium and iron was 2:1;
[0061] (2) 37.8 mg of sodium borohydride was dissolved in 1 mL of deionized water and ultrasonicated for 1 h to obtain a uniformly dispersed solution B, wherein the ratio of the molar amount of sodium borohydride to the sum of the molar amounts of rhodium and iron was 5:1;
[0062] (3) Solution B was slowly added dropwise to solution A over a period of about 5 min, and stirred at 500 rpm for 1 h;
[0063] (4) 40 mg of ferric nitrate nonahydrate (0.1 mmol, 5.5 mg iron) was added to the above solution and stirred at 500 rpm for 1 h. The molar ratio of rhodium to iron was 1:1 and the iron loading was 1.1 wt.%;
[0064] (5) washing the solution by centrifugation with acetone and water in a volume ratio of 3:1, and repeating the process three times;
[0065] (6) The centrifuged sample was placed in a vacuum drying oven and dried at 80°C for 12 h, and the catalyst was collected for testing;
[0066] The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 8000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation. The reaction temperature was 270℃, the reaction pressure was 3MPa, the space velocity was 6000mL / g / h, and the volume ratio of CO2 / H2 was 1:4. The reaction performance test results are shown in Figure 2 .
[0067] The X-ray diffraction (XRD) spectra of the catalysts of Example 1 and Example 2 are as follows: Figure 1 As shown, from Figure 1 It can be seen that when the molar ratio of rhodium to iron is 1:2, the diffraction peak of iron oxide appears in the catalyst, indicating that some iron is agglomerated. When the molar ratio of rhodium to iron is 1:1, only the diffraction peak of the titanium dioxide carrier exists in the spectrum, and the diffraction peaks of rhodium and iron are not observed, indicating that rhodium and iron are evenly dispersed on the titanium dioxide carrier.
[0068] Example 3
[0069] (1) 50.6 mg of hydrated rhodium chloride (0.2 mmol, 19.8 mg of rhodium), 500 mg of nano-titanium dioxide (P25), and 66.6 mg of PVP (0.6 mmol, molecular weight calculated as monomer, PVP monomer molar mass is 111) were dissolved in 30 mL of deionized water, and stirred at 500 rpm for 1 h, which was recorded as solution A. The rhodium loading was 4 wt.%, the K value of PVP was 29-32, and the ratio of the molar amount of PVP to the sum of the molar amounts of rhodium and iron was 2:1;
[0070] (2) dissolving 56.7 mg of sodium borohydride in 1 mL of deionized water and ultrasonicating for 1 h to obtain a uniformly dispersed solution B, wherein the ratio of the molar amount of sodium borohydride to the sum of the molar amounts of rhodium and iron is 5:1;
[0071] (3) Solution B was slowly added dropwise to solution A over a period of about 5 min, and stirred at 500 rpm for 1 h;
[0072] (4) 40 mg of ferric nitrate nonahydrate (0.1 mmol, 5.5 mg iron) was added to the above solution and stirred at 500 rpm for 1 h. The molar ratio of rhodium to iron was 1:0.5 and the iron loading was 1.1 wt.%;
[0073] (5) washing the solution by centrifugation with acetone and water in a volume ratio of 3:1, and repeating the process three times;
[0074] (6) The centrifuged sample was placed in a vacuum drying oven and dried at 80°C for 12 h, and the catalyst was collected for testing;
[0075] The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 8000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation. The reaction temperature was 270℃, the reaction pressure was 3MPa, the space velocity was 6000mL / g / h, and the volume ratio of CO2 / H2 was 1:4. The reaction performance test results are shown in Figure 2 .
[0076] Example 4
[0077] (1) 25.3 mg of hydrated rhodium chloride (0.1 mmol, 9.9 mg rhodium), 500 mg of nano-titanium dioxide (P25), and 111 mg of PVP (1 mmol, molecular weight calculated based on monomer, PVP monomer molar mass is 111) were dissolved in 30 mL of deionized water, and stirred at 500 rpm for 1 h, which was recorded as solution A. The rhodium loading was 2 wt.%, the K value of PVP was 29-32, and the ratio of the molar amount of PVP to the sum of the molar amounts of rhodium and iron was 5:1;
[0078] (2) 37.8 mg of sodium borohydride was dissolved in 1 mL of deionized water and ultrasonicated for 1 h to obtain a uniformly dispersed solution B, wherein the ratio of the molar amount of sodium borohydride to the sum of the molar amounts of rhodium and iron was 5:1;
[0079] (3) Solution B was slowly added dropwise to solution A over a period of about 5 min, and stirred at 500 rpm for 1 h;
[0080] (4) 40 mg of ferric nitrate nonahydrate (0.1 mmol, 5.5 mg iron) was added to the above solution and stirred at 500 rpm for 1 h. The molar ratio of rhodium to iron was 1:1 and the iron loading was 1.1 wt.%;
[0081] (5) washing the solution by centrifugation with acetone and water in a volume ratio of 3:1, and repeating the process three times;
[0082] (6) The centrifuged sample was placed in a vacuum drying oven and dried at 80°C for 12 h, and the catalyst was collected for testing;
[0083] The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 8000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation. The reaction temperature was 270℃, the reaction pressure was 3MPa, the space velocity was 6000mL / g / h, and the volume ratio of CO2 / H2 was 1:4. The reaction performance test results are shown in Figure 2 .
[0084] Comparative Example 1 Catalyst prepared without introducing iron element
[0085] (1) 39.7 mg of hydrated rhodium chloride (0.15 mmol, 15.4 mg of rhodium), 500 mg of nano-titanium dioxide (P25), and 83.3 mg of PVP (0.75 mmol, molecular weight calculated as monomer, PVP monomer molar mass is 111) were dissolved in 30 mL of deionized water, and stirred at 500 rpm for 1 h, which was recorded as solution A. The rhodium loading was 3.1 wt.%, the K value of PVP was 29-32, and the ratio of the molar amount of PVP to the molar amount of rhodium was 5:1;
[0086] (2) Dissolve 28.4 mg of sodium borohydride in 1 mL of deionized water and sonicate for 1 h to obtain a uniformly dispersed solution B, wherein the molar ratio of sodium borohydride to rhodium is 5:1;
[0087] (3) Solution B was slowly added dropwise to solution A over a period of about 5 min, and stirred at 500 rpm for 1 h;
[0088] (4) washing the solution by centrifugation with acetone and water in a volume ratio of 3:1, and repeating the process three times;
[0089] (5) The centrifuged sample was placed in a vacuum drying oven and dried at 80°C for 12 h, and the catalyst was collected for later testing;
[0090] The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 8000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation. The reaction temperature was 270℃, the reaction pressure was 3MPa, the space velocity was 6000mL / g / h, and the volume ratio of CO2 / H2 was 1:4. The reaction performance test results are shown in Figure 2 .
[0091] Comparative Example 2 Catalyst prepared without introducing rhodium element
[0092] (1) 111.8 mg of ferric nitrate nonahydrate (0.28 mmol, 15.5 mg), 500 mg of nano-titanium dioxide (P25), and 155.4 mg of PVP (1.4 mmol, molecular weight calculated based on monomer, PVP monomer molar mass is 111) were dissolved in 30 mL of deionized water and stirred at 500 rpm for 1 h, recorded as solution A. The iron loading was 3.1 wt.%, the K value of PVP was 29-32, and the ratio of the molar amount of PVP to the molar amount of iron was 5:1;
[0093] (2) Dissolve 53 mg of sodium borohydride in 1 mL of deionized water and sonicate for 1 h to obtain a uniformly dispersed solution B, wherein the molar ratio of sodium borohydride to iron is 5:1;
[0094] (3) Solution B was slowly added dropwise to solution A over a period of about 5 min, and stirred at 500 rpm for 1 h;
[0095] (4) washing the solution by centrifugation with acetone and water in a volume ratio of 3:1, and repeating the process three times;
[0096] (5) The centrifuged sample was placed in a vacuum drying oven and dried at 80°C for 12 h, and the catalyst was collected for later testing;
[0097] The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 8000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation. The reaction temperature was 270℃, the reaction pressure was 3MPa, the space velocity was 6000mL / g / h, and the volume ratio of CO2 / H2 was 1:4. The reaction performance test results are shown in Figure 2 .
[0098] Comparative Example 3: Catalyst prepared without introducing dispersant
[0099] (1) 25.3 mg of hydrated rhodium chloride (0.1 mmol, 9.9 mg rhodium) and 500 mg of nano-titanium dioxide (P25) were dissolved in 30 mL of deionized water and stirred at 500 rpm for 1 h, which was recorded as solution A. The rhodium loading was 2 wt.%;
[0100] (2) 37.8 mg of sodium borohydride was dissolved in 1 mL of deionized water and ultrasonicated for 1 h to obtain a uniformly dispersed solution B, wherein the ratio of the molar amount of sodium borohydride to the sum of the molar amounts of rhodium and iron was 5:1;
[0101] (3) Solution B was slowly added dropwise to solution A over a period of about 5 min, and stirred at 500 rpm for 1 h;
[0102] (4) Add 40 mg of ferric nitrate nonahydrate (0.1 mmol, 5.5 mg iron) to the above solution and stir at 500 rpm for 1 h;
[0103] (5) washing the solution by centrifugation with acetone and water in a volume ratio of 3:1, and repeating the process three times;
[0104] (6) The centrifuged sample was placed in a vacuum drying oven and dried at 80°C for 12 h, and the catalyst was collected for testing;
[0105] The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 8000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation. The reaction temperature was 270℃, the reaction pressure was 3MPa, the space velocity was 6000mL / g / h, and the volume ratio of CO2 / H2 was 1:4. The reaction performance test results are shown in Figure 2 .
[0106] Comparative Example 4 Catalyst prepared by changing the reduction order
[0107] (1) 40 mg of ferric nitrate nonahydrate (0.1 mmol, 5.5 mg of iron), 500 mg of nano-titanium dioxide (P25), and 111 mg of PVP (1 mmol, molecular weight calculated as monomer, PVP monomer molar mass is 111) were dissolved in 30 mL of deionized water and stirred at 500 rpm for 1 h, which was recorded as solution A. The iron loading was 1.1 wt.%, the K value of PVP was 29-32, and the ratio of the molar amount of PVP to the sum of the molar amounts of rhodium and iron was 5:1;
[0108] (2) 37.8 mg of sodium borohydride was dissolved in 1 mL of deionized water and ultrasonicated for 1 h to obtain a uniformly dispersed solution B, wherein the ratio of the molar amount of sodium borohydride to the sum of the molar amounts of rhodium and iron was 5:1;
[0109] (3) Solution B was slowly added dropwise to solution A over a period of about 5 min, and stirred at 500 rpm for 1 h;
[0110] (4) 25.3 mg of hydrated rhodium chloride (0.1 mmol, 9.9 mg rhodium) was added to the above solution and stirred at 500 rpm for 1 h. The rhodium loading was 2 wt.%;
[0111] (5) washing the solution by centrifugation with acetone and water in a volume ratio of 3:1, and repeating the process three times;
[0112] (6) The centrifuged sample was placed in a vacuum drying oven and dried at 80°C for 12 h, and the catalyst was collected for testing;
[0113] The catalyst was pre-reduced with hydrogen before the reaction test. The pretreatment conditions were: hydrogen space velocity 8000mL / g / h, reduction temperature 300℃, and reduction time 2h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation. The reaction temperature was 270℃, the reaction pressure was 3MPa, the space velocity was 6000mL / g / h, and the volume ratio of CO2 / H2 was 1:4. The reaction performance test results are shown in Figure 2 .
[0114] The calculation process of CO2 conversion rate and selectivity is as follows:
[0115]
[0116] Among them, [CO2] inlet and [CO2] outlet Represent the molar concentration of CO2 in the raw gas and tail gas respectively.
[0117]
[0118] Among them, [CO], [C i H x ] and [CH4] represent the molar concentrations of CO, hydrocarbons and methane products, respectively.
[0119] from Figure 2 It can be seen that the catalyst prepared by the present invention exhibits high catalytic activity and methane selectivity; compared with the catalytic performance of the comparative catalyst, the rhodium-iron bimetallic catalyst prepared by the sequential reduction method can significantly enhance the activation ability of carbon dioxide, and at the same time has a strong hydrogenation ability, avoiding the desorption of carbon monoxide byproducts, and thus has excellent catalytic performance under low temperature conditions. Taking Example 4 as an example, under the condition of 270°C, the conversion rate of carbon dioxide is 98%, and the selectivity of methane can reach 99%.
[0120] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A method for preparing a rhodium-iron bimetallic catalyst, characterized in that: The following steps are involved: S1, dissolving nano-TiO2, rhodium salt and dispersant in water and stirring evenly to obtain solution A, wherein the content of rhodium ions is 1wt%-10wt% based on the mass of nano-TiO2; dissolving the reducing agent in water and obtaining a uniformly dispersed solution B after ultrasonic treatment; adding solution B dropwise to solution A and stirring to obtain solution C; S2, adding iron salt to solution C and continuing to stir evenly to obtain a mixed solution, wherein the molar ratio of rhodium to iron is 1:0.2-5; S3. Wash and dry the obtained mixed solution to obtain a rhodium-iron bimetallic catalyst.
2. The preparation method according to claim 1, characterized in that: In step S1, the rhodium salt is one or more of rhodium chloride, rhodium nitrate, rhodium phosphate, and rhodium acetylacetonate.
3. The preparation method according to claim 1, characterized in that: In step S1, the dispersant is polyvinyl pyrrolidone (PVP), and the model K value of PVP is 16 to 32; In step S1, the ratio of the molar amount of PVP to the total molar amount of rhodium and iron is 2 to 10:1; In step S1, the concentration of rhodium salt in solution A is 0.0006-0.05 g / mL.
4. The preparation method according to claim 1, characterized in that: In step S1, the reducing agent is one or more of sodium borohydride, sodium borohydride, ammonia borane, and hydrazine hydrate; The concentration of the reducing agent in solution B is 10 to 100 g / mL; In step S1, the ratio of the molar amount of the reducing agent to the total molar amount of rhodium and iron ions is 5 to 20:
1.
5. The preparation method according to claim 1, characterized in that: In step S1, the dropping speed is 0.1-0.5 mL / min, the stirring speed is 200-1000 r / min, and the stirring time is 0.5-2 h.
6. The preparation method according to claim 1, characterized in that: In step S2, the iron salt is one or more of ferric nitrate, ferric sulfate, ferric chloride, and ferric tribromide.
7. The preparation method according to claim 1, characterized in that: In step S2, the stirring speed is 200 rpm to 1000 rpm, and the stirring time is 0.5 h to 2 h.
8. A rhodium-iron bimetallic catalyst, characterized in that Prepared by the preparation method according to any one of claims 1 to 7, the rhodium-iron bimetallic catalyst comprises a nano-TiO2 carrier and highly dispersed rhodium-iron bimetallic nanoparticles supported on the nano-TiO2 carrier, and the average particle size of the rhodium-iron bimetallic nanoparticles is 5 to 20 nm; Based on the mass of the TiO2 carrier, the loading amount of rhodium is 1wt%-10wt%, and the molar ratio of rhodium to iron is 1:1-5.
9. Use of the rhodium-iron bimetallic catalyst according to claim 8 in the catalytic reaction of carbon dioxide hydrogenation to prepare methane.
10. The use according to claim 9, characterized in that: The catalytic reaction is carried out in a fixed bed reactor under the following reaction conditions: reaction temperature is 200-400°C, reaction pressure is 2-4MPa, gas space velocity is 3000-8000mL / g / h, and the gas used is a mixture of CO2 and H2, wherein the volume ratio of CO2 to H2 is 1:1-5; Preferably, the rhodium-iron bimetallic catalyst is subjected to hydrogen pre-reduction treatment before use, and the reduction conditions are: hydrogen space velocity of 3000mL / g / h to 10000mL / g / h, temperature of 200°C to 400°C, and reduction time of 0.5h to 5h.
Citation Information
Patent Citations
Catalyst used for methanation of carbon dioxide, preparation method therefor and applications thereof
CN104148065A
Application of rutile titanium oxide supported catalyst in carbon dioxide hydrogenation reaction
CN111036199A
Rhodium-iron double-metal hydrogenation catalyst as well as preparation method and application thereof
CN114471610A
Palladium-based bimetallic nano-catalyst as well as preparation method and application thereof
CN119897130A
Catalyst for low-temp. selective oxidation of CO in hydrogen gas and its preparation method
CN1428293A